2015
DOI: 10.1111/ijfs.12909
|View full text |Cite
|
Sign up to set email alerts
|

The impact of collagen on softening of grass carp (Ctenopharyngodon idella) fillets stored under superchilled and ice storage

Abstract: The objective of this work was to study the impact of collagen on softening of grass carp (Ctenopharyngodon idella) fillets during chilled storage. The fillets were stored under superchilling (À1.5 AE 0.2°C) and with ice (0.2 AE 0.1°C) for 21 days, and texture properties, collagen and the related enzyme activities were measured. Results showed that firmness and collagen content were strongly influenced by storage temperature and time. Fillet firmness decreased by 32.3% (superchilling) and 49.6% (ice stored) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In addition to volatile flavors of grass carp, most of them focused on the influence of storage conditions on the texture and quality changes of grass carps fillets. (Ge, Xu, & Xia, ; Jiang, Xu, Ge, Xia, & Jiang, ; Yin, Luo, Fan, Wu, & Feng, ). To our best knowledge, no previous study on volatile flavor components in different parts of grass carp.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to volatile flavors of grass carp, most of them focused on the influence of storage conditions on the texture and quality changes of grass carps fillets. (Ge, Xu, & Xia, ; Jiang, Xu, Ge, Xia, & Jiang, ; Yin, Luo, Fan, Wu, & Feng, ). To our best knowledge, no previous study on volatile flavor components in different parts of grass carp.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also found that the decreasing tendency of collagenase activity was more obvious in superchilled fillets than in ice‐stored samples (Jiang et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…This result was in accordance with previous reports that stated that the total collagen content tended to decline, and this declining trend was more significant during ice storage (Jiang et al . ). The different changes in collagen contents in fillets treated with different additives may be attributed to the difference in the inhibitory activity on collagenase in fillets.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations